STRATEGI PENGEMBANGAN BISNIS UMKM JAMU TRADISIONAL MADURA MELALUI PENDEKATAN ANALISIS SWOT (Studi Kasus: UMKM Jamu Tradisional Madura di Kabupaten Pamekasan) - Rohematus Solehah; Resti Prastika Destiarni; Dewi Muti’ah (Universitas Galuh, 2022)
Madura is not only known as a center for the production of salt and tobacco commodities, but this famous dry island is also famous for its traditional herbal medicine ingredients. Pamekasan is a district that is famous for its processed biopharmaceuticals in the form of traditional herbal medicine. Some of the objectives of this research are: To classify traditional herbal medicine businesses in the category of micro, small and medium enterprises based on their characteristics and analyze the strategy for implementing the partnership model through SWOT. This research was carried out in Pamekasan Regency, and was carried out from June–November 2021. This research is a qualitative research in which the data sources are obtained from questionnaires and the results of interviews with Madurese traditional herbal medicine entrepreneurs. This study was analyzed using two analytical tools, namely descriptive analysis and SWOT analysis. Based on the results of the IFE calculation, a total score of -0.168 was obtained and the EFE calculation obtained a total score of 0.686. The results of these calculations show that the IE matrix (Internal External) of herbal medicine SMEs in Pamekasan Regency is in quadrant IX, this shows that herbal medicine SMEs in Pamekasan Regency have a low average value, so the right strategy to use is the strategy to support the diversification strategy. . The strategy applied in this condition is to minimize weaknesses to reduce threats.